Literature Review: The Ability of Mathematical Connection to Learning Outcomes - Ismunandar, Denni; Nurhayani, Siti; Nandang, Nandang (Universitas Wiralodra, 2024)
This study aims to analyze students' mathematical connection abilities through the Systematic Literature Review (SLR) approach. The main focus of the study is to identify the influence of learning strategies such as Problem-Based Learning (PBL), Realistic Mathematics Education (RME), and project-based learning on mathematical connection skills. This study analyzed 11 articles published in the 2022–2024 time frame. The results of the review show that innovative learning approaches, such as PBL and RME, have a significant positive impact on improving students' mathematical connection skills. Factors such as motivation, mathematical resilience, and learning environment were also found to be important elements influencing the success of the strategy. In addition, these results provide practical recommendations for teachers to integrate mathematical connections in the learning process as well as encourage further research on the influence of technology, culture, and socio-economic conditions on mathematical connection ability